Separation of Liquid Pig Manure - Matzen, Ricard (agricultural engineering.eu, 1999)
This paper reports the function and warlangresults from a pilotplant in which liquid pig manure was flocculated with Gekobentonite. The supernatant was irrigated an agriculturall and throughout the year,in wintertime, only after ion exchange of ammonium with Agrolith. Earlier Iabaratory research showed that it is possible to purify the liquid to the concentration wanted, although higher puritycosts more. The thicker slurry fraction was stored and treated as ordinary liquid manure. In order to maintain ability for pumping, the treatment was stopped at approximately 12 % dry matter content and it represents a concentration of the liquid manure to approximately one-quarter or one-third of the original volume.